2012
DOI: 10.1071/fp11206
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant dendrometer and leaf patch pressure probe measurements reveal the effect of microclimate and soil moisture on diurnal stem water and leaf turgor variations in young oak trees

Abstract: Tree water relations and their dependence on microclimate and soil moisture were studied over several months in young oaks (Quercus robur L.) subjected in large lysimeter-based open top chambers to environments with a controlled soil water supply. Automated single point dendrometers and the recently developed leaf patch clamp pressure (LPCP) probe were used for monitoring water-related stem radius variations (ΔW) and turgor-dependent leaf patch pressures (Pp). Both parameters showed distinct diurnal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 34 publications
4
57
2
3
Order By: Relevance
“…As observed in other studies (Zimmermann et al, 2008Ehrenberger et al, 2012), there are some indications to be used for the evaluation of drought using probes such as the following: enhancing Pp peaks at noon (when this increase becomes maximum, it is also called Pp peak or Pp max), increasing Pp night values (increase of minimum values), and Pp recovery between maximum and minimum values. Height growth (cm) in maize plants during 30 days of treatment, representing the whole cycle of analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed in other studies (Zimmermann et al, 2008Ehrenberger et al, 2012), there are some indications to be used for the evaluation of drought using probes such as the following: enhancing Pp peaks at noon (when this increase becomes maximum, it is also called Pp peak or Pp max), increasing Pp night values (increase of minimum values), and Pp recovery between maximum and minimum values. Height growth (cm) in maize plants during 30 days of treatment, representing the whole cycle of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the leaf pressure transfer function and thus the attenuation of the constant external pressure, is dictated by a plant-specific, turgor pressure-independent term and a turgor pressure-dependent term (Westhoff et al, 2009). The behavior of many plants, like banana , olives (Fernandez et al, 2011;Ben-Gal et al, 2010), wheat (Bramley et al, 2013), grapevines , canola (Kant et al, 2014) and oak (Ehrenberger et al, 2012) were tested and concluded that this technique have highly precision to measure water status in intact plants. However, there is no observation for maize yet.…”
Section: Introductionmentioning
confidence: 99%
“…Very little is known about the impact of this bark degradation on SR and about its timing; it may mainly take place during the dormancy period. This aspect is thus not further addressed in this study. Any water‐related processes affecting the SR are driven by water potential gradients in the tree, which are mainly induced by transpiration and altered by water availability in the soil, by temperature‐dependent hydraulic flow limitations (Zweifel et al ., ; Ehrenberger et al ., ; Steppe et al ., ; Dawes et al ., ), and by osmotic processes in the bark (De Schepper & Steppe, ; Sevanto et al ., ; Mencuccini et al ., ; Chan et al ., ). The transpiration‐induced tension in the xylem (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The partitioning procedure can be carried out retrospectively only, because it needs information about all SR peaks in a time‐series. One parameter needs to be set to define the maximum temporal range between two neighbouring SR peaks (Zweifel et al ., ), affecting the slope of the growth. The ZG concept results in a GRO curve with a stepwise shape (Deslauriers et al ., ,b, ; Drew & Downes, ; Ehrenberger et al ., ) with the assumption of no growth during periods of stem shrinkage (i.e. increased TWD).…”
Section: Introductionmentioning
confidence: 99%
“…Bark time series were detrended for growth in order to use it as a direct measure of water deficit in trees. For this, the growth line of the species was determined, based on the local maximum values of stem radius (Zweifel et al, 2005;Ehrenberger et al, 2012). The actual water deficit was calculated by subtracting the measured changes in stem radius from the growth line.…”
Section: Methodsmentioning
confidence: 99%